Brand Positioning and the Consumer Mind Case Study: Maggi Noodles (Global Journal of Management and Business Research, 2023)
This research paper discusses Brand Positioning and its effects on the Consumer Mind Brand Positioning refers to positioning a particular brand in the consumer s mind using its unique features usage emotions etc There are various ways in which brands position themselves in the minds of consumers from comparative differentiation and value-based to lifestyle and many more A good brand positioning strategy answers basic questions like who the target market is what features the product provides and how it is different from other products All these features have been discussed in detail